Advances in steel structures : proceedings of the fourth International Conference on Advances in Steel Structures, 13-15 June 2005, Shanghai, China - International Conference on Advances in Steel Structures (4th : 2005 : Shanghai, China); Shen, Z. Y.; Li, G. Q.; Chan, S. L. (Amsterdam : Elsevier, 2005)
09